Technical and economic viability of drip irrigation of coffee in Araxá, MG - Fernandes, André Luís Teixeira; Tavares, Tiago de Oliveira; Santinato, Felipe; Ferreira, Rodrigo Ticle; Santinato, Roberto (Coffee Science - ISSN 1984-3909, 2016)
: In the region of Araxá highlands, the economical production of coffee is traditionally made without irrigation. Notwithstanding in recent years, with climate change, water deficit of 150 mm have been verified, affecting the vegetative and productive development of the culture. Within this context, the aim of this study was to evaluate supplementary irrigation to increase production and profitability of the coffee grown in the highlands of Araxá, compared to a non-irrigated and irrigated cultivation throughout the year. The work was implemented in Araxá, Minas Gerais in 2006 and carried out throughout the period of nine years. Different periods of water stress (from April to November) were evaluated, compared with irrigation throughout the year and the witness. After 6 consecutive harvests, it can be concluded that supplemental irrigation promoted an increased productivity in the coffee grown under the conditions of the Araxá Plateau, especially in years of drought. With regard to economic performance, the process of irrigation applied throughout the year promoted profits of 279% (R/ha year-1) compared to the treatment without irrigation.